Perusahaan Keluarga dan Penghindaran Pajak di Indonesia: Moderasi Koneksi Politik - Rini Adriani Auliana; Siti Fatimah; Baiq Anggun Hilendri (Akuisisi : Jurnal Akuntansi, 2025)
This study aims to analyze family firms' ability to limit tax avoidance and analyze political connections in weakening the influence of family firms in limiting tax avoidance. This study uses three research proxies: Effective Tax Rate (ETR), Cash Effective Tax Rate (CETR), and Book Tax Differences (BTD). The study population is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020-2023. The sample selection used a purposive sampling technique, resulting in 92 company samples with 276 observations. The results show that family firms can limit tax avoidance using the Book Tax Differences (BTD) proxy. Other results show that political connections can weaken the influence of family firms in limiting tax avoidance using the Effective Tax Rate (ETR) and Cash Effective Tax Rate (CETR) proxies. Family firms tend to avoid tax avoidance to maintain their reputation. Political connections held by family firms can result in overpowering them, thus increasing the opportunity for tax avoidance.